Interactive Multimedia Based on Cognitive Conflict Integrated with Character Animation and Science Literacy Indicators on Alternative Energy Material - Rahmadani, Anisya; Mufit*, Fatni; Fathanah, Zahra (Universitas Syiah Kuala, 2025)
This investigate was conducted by planning intuitively mixed media based on cognitive strife coordinates with character liveliness to progress students' science proficiency on elective vitality materials. The reason of this think about was to clarify the characteristics, analyze the legitimacy and common sense of intelligently mixed media with cognitive struggle models on elective vitality materials. This sort of inquire about is plan investigate utilizing the Plomp advancement show. This investigate starts with the Essential Inquire about arrange and is constrained to the one to one organize as it were. Data collection was carried out by conducting self-assessment (self evaluation), distributing instruments for 2 teachers and science literacy-based questions for students, and at the one to one stage the research was carried out by testing the practicality of interactive multimedia by 3 students with high, medium and low abilities. The results of research at the preliminary research stage or the preliminary stage found that only 47.6% understood literacy. At the stage of development/pototyping phase interactive multimedia is prepared using cognitive conflict model syntax. At the self evaluation stage, the average of each component is 78.3% with a good category. The validity results obtained an average of 0.9 with very valid criteria. The results of practicality obtained an average of 90% with a very high category. The conclusion of the research conducted is that interactive multimedia based on cognitive conflict integrated with character animation on alternative energy materials can facilitate students' science literacy. So that it can be continued at the effectiveness stage